The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0091756
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in IgA Nephropathy: 30-Year Analysis of 1,012 Patients at a Single Center in Japan

Abstract: BackgroundLittle is known about the long-term prognosis of patients with IgA nephropathy (IgAN).MethodsThis retrospective cohort analysis evaluated clinical and histological findings at the time of renal biopsy, initial treatment, patient outcomes over 30 years, and risk factors associated with progression in 1,012 patients diagnosed with IgAN at our center since 1974.ResultsOf the 1,012 patients, 40.5% were male. Mean patient age was 33±12 years and mean blood pressure was 122±17/75±13 mmHg. Mean serum creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 30 publications
9
140
8
2
Order By: Relevance
“…IgAN is not a benign disease; according to a retrospective cohort analysis evaluated clinical and histological findings in 1012 patients diagnosed with IgAN, with about 50% of patients progressing to ESRD within 30 years despite treatment, this study also shown that tonsillectomy plus steroids dramatically improved renal outcome. 17 Although the recent Kidney Disease:…”
Section: Discussionmentioning
confidence: 99%
“…IgAN is not a benign disease; according to a retrospective cohort analysis evaluated clinical and histological findings in 1012 patients diagnosed with IgAN, with about 50% of patients progressing to ESRD within 30 years despite treatment, this study also shown that tonsillectomy plus steroids dramatically improved renal outcome. 17 Although the recent Kidney Disease:…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria decreased by a median of 0.5 g/24h during follow-up. Overall, the median number of creatinine, proteinuria, and blood pressure measurements was 5 (3)(4)(5)(6)(7)(8), 4 (3-7), and 5 (3)(4)(5)(6)(7)(8), respectively.…”
Section: Study Cohortmentioning
confidence: 99%
“…Sixteen such studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , including cohorts from Europe, North America, and East Asia were meta-analysed in a report published in 2013 21 . Lately, more studies have been published including cohorts from Iran, Europe, Japan and Korea [22][23][24][25][26][27][28] . All these studies are summarised in Supplementary Table 1.…”
Section: Published Retrospective Validation Studiesmentioning
confidence: 99%